2019
DOI: 10.1186/s12882-019-1620-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and outcomes of acute kidney injury in South African critically ill adults: a prospective cohort study

Abstract: BackgroundThere is a marked paucity of data concerning AKI in Sub-Saharan Africa, where there is a substantial burden of trauma and HIV.MethodsProspective data was collected on all patients admitted to a multi-disciplinary ICU in South Africa during 2017. Development of AKI (before or during ICU admission) was recorded and renal recovery 90 days after ICU discharge was determined.ResultsOf 849 admissions, the mean age was 42.5 years and mean SAPS 3 score was 48.1. Comorbidities included hypertension (30.5%), H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 49 publications
(58 reference statements)
4
32
1
Order By: Relevance
“…In our study, we demonstrate that male sex, a history of hypertension and CKD were significant predictors of AKI. Hypertension is a recognised risk factor for AKI among African patients [ 9 ], although this is not a consistent finding [ 24 ]. Comorbidities, such as hypertension, are increasingly prevalent in sub-Saharan Africa [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we demonstrate that male sex, a history of hypertension and CKD were significant predictors of AKI. Hypertension is a recognised risk factor for AKI among African patients [ 9 ], although this is not a consistent finding [ 24 ]. Comorbidities, such as hypertension, are increasingly prevalent in sub-Saharan Africa [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Livingstone Tertiary Hospital serves approximately 1.6 million people from an area of 60 000 km2. The data was extracted from the database of an observational ICU study: Acute kidney injury in critically ill patients in a tertiary intensive care unit in the Eastern Cape, South Africa (the LivAKI study) which included 875 ICU admissions to Livingstone Tertiary Hospital (LTH) Adult ICU [15]. All first time ICU admissions 12 years and older, admitted from the 3rd of January 2017 to the 2nd January 2018 were included.…”
Section: Study Methodsmentioning
confidence: 99%
“…The study found that AKI had an incidence of 15% when using the RIFLE classification. [6] Moreover, patients with AKI had an overall mortality of 57%, and 38% (n=39) of the patients with AKI required renal replacement therapy Another prospective study by Aylward et al [7] evaluated 849 admissions to the ICU and found that the common reason for admission was trauma (26%) and that AKI was associated with a higher in-hospital mortality rate of 31.8% compared with 7.23% in those without AKI. [7] A study by Bagshaw et al [8] found that 42.1% (n=14 039) of the patients had concomitant AKI and 32.4% of these patients had sepsis, suggesting that a correlation might exist between AKI and sepsis.…”
Section: Articlementioning
confidence: 99%